Features of socio-pedagogical support guardian family - Kudasheva A. L. (Pedagogy, Psychology, Society, 2020)
The issues of the vital activities of the guardian family and the existing problems in providing her with social and pedagogical support from the guardianship and trusteeship authorities are revealed. The main forms and methods of interaction with a guardian family are described, affecting its educational potential and the goodwill of relations between children and adults in the family. The results of the diagnosis are described and analyzed, showing the main difficulties that require targeted cooperation of adults to improve psychological and pedagogical comfort in the life of a guardian family.
Keywords: попечительство; взаимоотношения; relationships; Опекунская семья; социально-педагогическая поддержка; Guardianship family; guardianship and trusteeship; social and educational support; опека